What Have They Built You to Do? : The Manchurian Candidate and Cold War America - Jacobson, Matthew Frye, 1958- (Book collections on Project MUSE., 2006)
In What Have They Built You to Do?a key line of dialogue from the original filmMatthew Frye Jacobson and Gaspar Gonzlez undertake an ambitious reexamination of The Manchurian Candidate. Through their multifaceted analysis of the film in all its incarnations, Jacobson and Gonzlez raise provocative questions about power and anxiety in American politics and society from the Cold War to today.